2008
DOI: 10.1002/art.23373
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a patient with takayasu arteritis using a humanized anti–interleukin‐6 receptor antibody

Abstract: Takayasu arteritis (TA) is a chronic inflammatory disease that involves the aorta and its major branches. Since overproduction of interleukin-6 (IL-6) seems to play a pathogenic role in TA, we used the anti-IL-6 receptor (IL-6R) antibody tocilizumab to treat a 20-year-old woman with refractory active TA complicated by ulcerative colitis (UC). Treatment with tocilizumab improved the clinical manifestations of TA and the abnormal laboratory findings in this patient and ameliorated the activity of UC. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
1
16

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(88 citation statements)
references
References 12 publications
2
65
1
16
Order By: Relevance
“…33) In a refractory patient with TA, Nishimoto, et al reported that the serum TNF-α level fluctuated during TCZ therapy while the disease activity was well-controlled. 19) Taken together, these fi ndings indicate that TNF-α is upstream of IL-6 in the infl ammatory cytokine cascade and that TNF-α therapy may have a therapeutic effect in refractory patients with TA via the indirect reduction of IL-6 production.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…33) In a refractory patient with TA, Nishimoto, et al reported that the serum TNF-α level fluctuated during TCZ therapy while the disease activity was well-controlled. 19) Taken together, these fi ndings indicate that TNF-α is upstream of IL-6 in the infl ammatory cytokine cascade and that TNF-α therapy may have a therapeutic effect in refractory patients with TA via the indirect reduction of IL-6 production.…”
Section: Discussionmentioning
confidence: 72%
“…In 2008, Nishimoto, et al reported the successful treatment of a patient with refractory TA accompanied by ulcerative colitis with TCZ. 19) TCZ (4 mg/kg/weekly and biweekly) rapidly induced improvements in the clinical manifestations and laboratory data, along with partial recovery of the ischemic symptoms. 19) In 2011, Seitz, et al reported that TCZ (8 mg/kg) was also effective in 7 patients with LVV (5 with GCA and 2 with TA) for a mean period of 4.3 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RA (in more than 90 countries worldwide) [36][37][38][39][40][41][42] Castleman's disease (in Japan) [52,53] Systemic and polyarticular JIA (in Japan) [57][58][59] Candidate diseases for tocilizumab therapy: Systemic autoimmune diseases SLE [130] Systemic sclerosis [115] Giant cell arteritis and Takayasu arteritis [90,91] Polymyositis Organ specific autoimmune diseases Crohn's disease [73] Relapsing polychondritis [108] Multiple sclerosis, neuromyelitis optica Acquired hemophilia A [149] Chronic inflammatory diseases Adult-onset Still's disease [61][62][63][64][65][66][67][68] Reactive AA amyloidosis [48][49][50][51] Polymyalgia rheumatica [80,91] RS3PE [85] Spondyloarthritides [100,[102][103][104][105] Behcet's disease Uveitis GVHD [150] Autoinflammatory diseases (TRAPS) [152] Tocilizumab has been approved as a biological drug for the treatment of RA, Castleman's disease and juvenile idiopathic arthritis, and is expected to be applicable to various other autoimmune and inflammatory diseases. Abbreviations: RA, rheumatoid arthritis; JIA, juvenile idiopathic arthritis; SLE, systemic lupus erythematosus; RS3PE, remitting seronegative, symmetrical synovitis with pitti...…”
Section: Conflict Of Interestmentioning
confidence: 99%